Clegg, Roger, and Lucie Skeaping. Singing Simpkin and other Bawdy Jigs: Musical Comedy on the Shakespearean Stage, Scripts, Music and Context. Exeter: U of Exeter P, 2014. 340 pp. - Rouse, Andrew C. (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Singing Simpkin is long overdue. Not only as an invaluable addition to the Renaissance drama library but as a statement about what a typical Elizabethan/Jacobean theatre entertainment comprised. Where a decade ago Duffin’s book (with enclosed CD), Shakespeare’s Songs, finally put the musical elements of Shakespeare’s plays into their rightful, more central context, here Roger Clegg (senior lecturer in Drama Studies at De Montfort University) and Lucie Skeaping (presenter of the BBC’s The Early Music Show and performer—the City Waites), both of whom regularly work with the Globe Theatre, now provide us with an image of the entire raucous entertainment package, only a part of which was the Shakespeare play itself.